From simulation to evidence-based practice: SoTL evaluation of a learning design in paramedic higher education. - Hofmann, Thomas (HeilberufeSCIENCE, 2026)
Simulation is well established in paramedic education, but it is often used primarily to rehearse clinical performance rather than to support evidence-based practice (EBP). This Scholarship of Teaching and Learning study explored whether a simulation-to-EBP learning design was associated with changes in EBP self-efficacy in a German top-up BSc paramedic science program. In an exploratory single-group pre–post design, students completed the German Evidence-Based Practice Confidence (EPIC) scale on the day before and the day after a traumatology block day. The intervention combined trauma simulations, student-generated decision points, focused literature searching, and plenary discussion. In total, 14 matched cases were available for analysis. Total scores on the EPIC increased significantly from pre-test to post-test—t(13) = 5.887, p < 0.001, dz = 1.573, gz = 1.480—with 10 of 14 participants exceeding the MDC95. Significant item-level gains were observed in question formulation, critical appraisal, applicability, decision-making, and evaluation.